Strategi Pengembangan Perikanan Tangkap di Kecamatan Gerokgak Kabupaten Buleleng - KIRYEMAN, AGNESIA PRISKILA; ARTINI, NI WAYAN PUTU; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Catch Fisheries Development Strategy in Buleleng District Gerokgak Sub-district. The fishing community has a special characteristic that distinguishes the from other communities and fishermen is synonymous with poverty, the large number of childern in families and low education. The aim of this study is to determine fisheries in Buleleng District and understand the socioeconomic conditions of catch fisheries in Buleleng District. Research methods use SWOT analysis. The life span of a fisherman is dominated by a 15-64 year old and the rate of a fisherman’s education in Gerokgak District is basic education level. In general the conditions of the fleet and catch equipment used are still smal in scale fishing, with the average amount of fishing income of Rp. 1.000.000-2.000.000 per month. The suggested development strategy is to build partnerships with homes and hotels in Gerokgak District, development of captured products, to discuss opportunities of catch fishing with service, to provide capture delivery services, to improve capture fisheries by adding tools, to consult related services on the addition of captured fisheries infrastructure, providing cooperation with financial institutions to boost fisheries’ investment capital, increasing fishermen’s outlook on the importance of technology, modern capture tools, and how to wor with business sustainers, bringing capital owners to invest in fishing through promotions, using profitable sales prices for increased tools and arrest fleets, meeting with related services to discuss the need for government support in adding more modern bust fleets, and socializing of profitable marketing channels and the importance of protecting the environment can increase fisheries resources.